Humanity and Dignity Through Knowledge: A Ten-Year Vision - Feinstein International Center (Tufts Archival Research Center, 2005)
We have a vision of a future ten years from now in which famine, widespread violations of human rights, extreme suffering and crimes against humanity are held to be self-evidently unacceptable by states and their peoples. A vision in which nation states, and the international community, in all its manifestations, feel duty bound to act -- and do act -- to prevent and alleviate such abuses.